A Novel Rotablator Technique (Low-Speed following High-Speed Rotational Atherectomy) Can Achieve Larger Lumen Gain: Evaluation Using Optimal Frequency Domain Imaging. (20th May 2019) - Yamamoto, Takanobu; Yada, Sawako; Matsuda, Yuji; Otani, Hirofumi; Yoshikawa, Shunji; Sasaoka, Taro; Hatano, Yu; Umemoto, Tomoyuki; Ueshima, Daisuke; Maejima, Yasuhiro; Hirao, Kenzo; Ashikaga, Takashi
Abstract : Background. While the evaluation of burr speed was discussed regarding platelet aggregation, the association between platform speed and acute lumen gain of rotational atherectomy remains unknown. Methods. Through the evaluation of the potential of low-speed rotational atherectomy (LSRA) in in-vitro experiments, minimum lumen diameter (MLD) and minimum lumen area (MLA) after conventional high-speed rotational atherectomy (HSRA group) and those after LSRA following HSRA (LSRA+HSRA group) treated by 1.5 mm burrs were measured by optical frequency domain imaging (OFDI) in 30 consecutive human lesions. Results. The in-vitro experiments demonstrated that MLD and MLA after LSRA+HSRA were significantly larger (MLD: LSRA+HSRA=1.50 ±0.05 mm, HSRA= 1.43 ±0.05 mm, p=0.015; MLA: LSRA+HSRA= 1.90 ±0.17 mm 2, HSRA= 1.71±0.11 mm 2, and p= 0.037), requiring more crossing attempts (LSRA= 134 ±20 times, HSRA= 72 ±11 times, and p< 0.001). In human studies, there was no significance in reference vessel diameter and lesion length before the procedure between two groups. MLDs after LSRA+HSRA were significantly larger than those in HSRA (LSRA+HSRA= 1.22 ±0.16 mm, HSRA= 1.07 ±0.14 mm, and p= 0.0078), while MLAs after LSRA+HSRA tended to be larger (LSRA+HSRA= 1.79 ±0.51 mm 2, HSRA= 1.55 ±0.47 mm 2, and p= 0.19). There was no significance in the occurrence of in-hospital complication, including slow flow or no reflow, major dissection, and procedural myocardial infarction, between LSRA+HSRA and HSRA. Conclusions. LSRA can achieve larger lumen gain compared, whereas HSRA can pass calcified lesions easily. Combination of LSRA and HSRA is a safe and feasible strategy for severely calcified lesions in clinical practice.